Does early child care attendance influence children's cognitive and non-cognitive skill development? - Daniel Kuehnle; Michael Oberfichtner (Friedrich-Alexander-Universität Erlangen-Nürnberg, Lehrstuhl für Arbeitsmarkt- und Regionalpolitik, 2017)
While recent studies mostly find that attending child care earlier improves the skills of children from low socio-economic and non-native backgrounds in the short-run, it remains unclear whether such positive effects persist. We identify the short- and medium-run effects of early child care attendance in Germany using a fuzzy discontinuity in child care starting age between December and January. This discontinuity arises as children typically start formal child care in the summer of the calendar year in which they turn three. Combining rich survey and administrative data, we follow one cohort from age five to 15 and examine standardised cognitive test scores, non-cognitive skill measures, and school track choice. We find no evidence that starting child care earlier affects children's outcomes in the shortor medium-run. Our precise estimates rule out large effects for children whose parents have a strong preference for sending them to early child care. – – Dieser Beitrag untersucht anhand detaillierter Befragungsdaten und administrativer Daten die mittelfristigen Auswirkungen eines früheren Kindergartenbesuchs auf kognitive und nicht-kognitive Fähigkeiten von Kindern in Deutschland. Um den kausalen Effekt zu identifizieren, nutzen wir eine Diskontinuität im durchschnittlichen Alter bei Kindergartenbeginn zwischen Kindern, die vor und nach dem Jahreswechsel geboren sind. Wir finden weder Belege, dass sich ein früherer Kindergartenbesuch auf kognitive Fähigkeiten, nicht-kognitive Fähigkeiten oder den besuchten Schultyp im Alter von etwa 15 Jahren auswirkt, noch zeigen sich kurzfristige Effekte im Alter von etwa fünf Jahren. Die präzisen Schätzungen schließen starke Effekte aus. Unsere Ergebnisse legen nahe, dass die Fähigkeiten von Kindern, deren Eltern starke Präferenzen für einen frühen Kindergartenbesuch haben, nicht von einem tatsächlichen, frühen Kindergartenbesuch beeinflusst werden.
Keywords: J13; I21; I38; 330; child care; child development; skill formation; cognitive skills; non-cognitive skills; fuzzy regression discontinuity